Peripheral Injection of hUC-MSCs in the Treatment of Acute Liver Failure: A Pre-Clinical Cohort Study in Rhesus Monkeys - Yuting Zeng; Zhenru Wu; Gen Chen; Guoqiang Liu; Bo Zhang; Yongjie Zhou; Menglin Chen; Rong Yao; Yujun Shi (Hindawi Limited, 2024)
Background. Using a toxin-induced lethal acute liver failure (ALF) monkey model, we have recently shown that early peripheral infusion of human umbilical cord mesenchymal stem cells (hUC-MSCs) can alleviate liver damage and improve animal survival by suppressing the activation of circulating monocytes and the subsequent cytokine storm. Here, we explored whether the administration of hUC-MSCs could still improve ALF when the cytokine storm is fully developed. Method. We treated ALF monkeys with peripheral delivery of hUC-MSCs at 48 hr after toxin challenge. Liver indices, histology, imaging, and animal survival were recorded and analyzed. Results. In our cohort study, we conducted and demonstrated that the infusion of hUC-MSCs significantly improved liver histology, effectively controlled inflammatory cytokine storms, and increased survival rates. Additionally, the administration of a higher dose of hUC-MSCs (2 × 107/monkey) yielded superior outcomes compared to a lower dose (1 × 107/monkey). Conclusion. Treatment of hUC-MSCs can significantly improve the pathological and survival outcomes of ALF even when the cytokine storm has been fully developed, indicating a promising clinical solution for ALF.